2020
DOI: 10.1101/2020.09.17.301887
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An accurate aging clock developed from the largest dataset of microbial and human gene expression reveals molecular mechanisms of aging

Abstract: Accurate measurement of the biological markers of the aging process could provide an “aging clock” measuring predicted longevity and allow for the quantification of the effects of specific lifestyle choices on healthy aging. Using modern machine learning techniques, we demonstrate that chronological age can be predicted accurately from (a) the expression level of human genes in capillary blood, and (b) the expression level of microbial genes in stool samples. The latter uses the largest existing metatranscript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…Immunotherapy is a tumor therapy that utilizes the human body's immune system to generate an antitumor response, providing a new therapeutic approach for the treatment of HCC [32][33][34] , especially the application of immune checkpoint inhibition, with better objective remission rate and longer progressionfree survival time for HCC patients [35] . Our study found that FRGs in 3 were associated with high expression of B cells, macrophages, and dendritic cells in high-risk HCC patients and were associated with prognosis, re ecting that iron death may be involved in the regulation of the immune microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Immunotherapy is a tumor therapy that utilizes the human body's immune system to generate an antitumor response, providing a new therapeutic approach for the treatment of HCC [32][33][34] , especially the application of immune checkpoint inhibition, with better objective remission rate and longer progressionfree survival time for HCC patients [35] . Our study found that FRGs in 3 were associated with high expression of B cells, macrophages, and dendritic cells in high-risk HCC patients and were associated with prognosis, re ecting that iron death may be involved in the regulation of the immune microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Biological age (also referred to as physiological age), which might be lower or higher than the chronological age, describes the real age-related functional status of an individual based on health biomarkers. Aging clocks are means of predicting a person’s biological age based on individualized inputs [ 44 ] such as inflammatory profile [ 45 ], epigenetic [ 46 ], transcriptomic [ 47 , 48 , 49 ], proteomic [ 50 , 51 , 52 ], and metabolomic age predictors [ 53 , 54 ]. A useful biological age predictor must be easily collected (and as noninvasive as possible), require low-cost processing, and be dynamically responsive to environmental and medical interventions, which are known to constitute critical factors for determining lifespan and health.…”
Section: The Aging Clocksmentioning
confidence: 99%
“…These included decreased vitamin B12 synthesis, reduced reductase activity, increased DNA damage, stress, immune system impairment, and upregulated glycosyltransferases. Using a metatranscriptomic analysis pipeline, Gopu et al [ 48 ] suggested that microbial expression patterns could be used to predict biological age. By analyzing meta-transcriptomic profiles of approximately 90,000 individuals, aged between 0 and 104 years old, with a wide array of lifestyle habits and disease states (e.g., digestive and metabolic disorders), a strong positive correlation was identified between the microorganisms’ functional profiles, which are related to methanogenesis pathways, and age.…”
Section: The Aging Clocksmentioning
confidence: 99%
See 2 more Smart Citations